Analysis of Tourists Willingness to Pay Using the Contingent Valuation Method Approach "Case Study of the Bedengan Forest Tourism Area in Selorejo Village, Malang Regency" - Wardana, Fitri Candra; Abidin, Zainul; Atikawati, Dini; Sudaryanti, Sri; Hidayati, Bunga; Parmawati, Rita; Fuad Al Fatih, Ahmad Nuril; Malik, Muhammad Adam (Journal of Indonesian Tourism and Development Studies, 2024)
Forest ecosystems experience pressure and degradation of environmental services, which is thought to be due to community activities such as land conversion for economic purposes. In previous research at the same location, there was still no calculation of the willingness to pay for environmental services from visiting tourists. Therefore, this research was conducted to determine the value of tourists' willingness to pay, which can be used for the management and development of tourist areas. This research uses CVM (Contingent Valuation Method) to estimate the costs that will be incurred by the community, particularly visitors. The results of research through surveys show that the public's perception of Bedengan Selorejo provides an overview of the most dominant tourist attributes, namely: attractions, accessibility, and amenities. The estimated size of the community's WTP (Willingness To Pay) for the value of the existence of a forest ecosystem is IDR. 450,208,000/month. The recommendation based on the results obtained is that this value can be used for the development and management of the Bedengan Selorejo tourist area in Malang Regency, ensuring that the ecosystem and facilities of this tourist attraction are well-maintained.